Strategi Pembelajaran Baca Tulis Al-Qur`An Dalam Meningkatkan Kemampuan Membaca Dan Menulis Al-Qur`an Pada Siswa SMP Swasta PAB 2 Helvetia - Aprilia, Aprilia (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This study aims to find out what learning strategies are used to Read and Write the Qur'an in Improving the Ability to Read and Write the Qur'an at Private Middle School PAB 2 Helvetia. What are the teacher's efforts in improving the ability to read and write the Qur'an in students. What are the supporting and inhibiting factors of learning strategies to read and write the Koran in improving the ability to read and write the Koran in students of Private Middle School PAB 2 Helvetia. This type of research is a qualitative description with qualitative methods. Sources of data in this study are primary data obtained by direct observation in the field and secondary data obtained by conducting in-depth interviews with informants. The results of this study state that: 1). The learning strategies used by Islamic Religious Education teachers in improving their ability to read and write the Koran are direct instruction and indirect instruction. 2). The teacher's efforts to improve students' reading and writing of the Qur'an are grouping students through reciting together with PAI teachers for those who can already read the Koran and the BTQ program for students who cannot yet read the Koran. 3). The methods used by religious education teachers are the Iqra` method, and the imla` method. Supporting factors are: Islamic Religious Education teachers who assist in educating and guiding the reading and writing of the Qur'an, as well as the attention and interest of students in learning to read and write the Qur'an, and parents who educate their children to recite the Koran at home or at school. Inhibiting factors arise from the students themselves, the various abilities and willingness of students. Homeroom teachers and PAI subject teachers who have more jobs and pay less attention to students. And varied family backgrounds.